Inhibition and kinetic studies on purified peroxidase from rhizome of turmeric (Curcuma longa L.) - Omowumi Funke Adedugbe; Olutosin Samuel Ilesanmi; Victory Ayo Olagunju; Ayodele O. Kolawole (Discover Chemistry)
Abstract The kinetics of substrate and inhibitor binding to purified peroxidase from rhizome of turmeric, as well as their possible interactions with the enzyme, were investigated employing in vitro and molecular docking techniques, respectively. This was with the view to providing information on the catalytic mechanism of the enzyme with substrate and inhibitors for various applications. The crude enzyme was purified in single step purification using aqueous two-phase partitioning system (ATPS). Lineweaver–Burk plots of initial velocity data at fixed and varying concentrations of the two substrates, catechol and hydrogen peroxide, showed linear patterns with intersection on the x-axis in the third quadrant suggesting sequential ordered bi bi mechanism of substrate addition to the peroxidase. The real kinetic constants − Kmcatechol and KmH 2 O 2 estimated from the secondary replots for the purified peroxidase from turmeric were 168 ± 2.0 mM and 87.4 ± 1.2 mM respectively. The Vmax obtained for the purified enzyme was 68,965 ± 50 units/mg protein. These led to first-order rate constant, kcat/Km of 0.49 × 106 M−1 s−1. All the inhibitors had inhibitory effect on the activity of ClP at varying concentrations. The inhibition constant (Ki) values for the inhibitors at increasing order are 0.4 mM for cysteine, 4.9 mM for ascorbic acid, 5 mM for citric acid and 9 mM for EDTA. Cysteine was the most potent inhibitor. From the docking simulation, the calculated docking score of the binding energy for ascorbic acid, citric acid, cysteine and EDTA were −8.988, −4.147, −3.361 and −2.206 kcal/mol respectively. The lower binding energy value of the inhibitor represents the higher affinity to the receptor protein. The binding interaction of the purified enzyme showed that ascorbic acid, citric acid and EDTA have 2 hydrogen bonds formed respectively while cysteine had 4 hydrogen bonds. The combination of kinetic and inhibition properties makes the enzyme a successful candidate to be employed for various applications in industrial and biotechnological processes.